2022
DOI: 10.1021/acsestengg.2c00219
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Volatile Fatty Acid Production from Food Waste Fermentation via Enzymatic Pretreatment: New Insights into the Depolymerization and Microbial Traits

Abstract: Food waste (FW) has been considered a potential carbon reservoir and can be used for high-value volatile fatty acid (VFA) production via anaerobic fermentation. Nevertheless, more work is needed to unravel how to regulate the structural defects of FW and enhance microbial metabolisms for improving VFA production through pretreatment methods. This work investigated the enhancement of VFA production from FW fermentation through enhancing depolymerization and stimulating microbial traits via enzymatic pretreatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Then, raw FASTQ files were demultiplexed and quality-filtered via QIIME, and chimeric sequences were recognized and eliminated using UCHIME. In addition, functional genes were predicted by PICRUSt2 analysis, which proved to be a valuable method for characterizing the functional capabilities of microbial populations . In comparison with other similar gene prediction strategies, such as Piphillin2, PanFP3, and Tax4Fun2, the PICRUSt2 prediction method was deemed superior …”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, raw FASTQ files were demultiplexed and quality-filtered via QIIME, and chimeric sequences were recognized and eliminated using UCHIME. In addition, functional genes were predicted by PICRUSt2 analysis, which proved to be a valuable method for characterizing the functional capabilities of microbial populations . In comparison with other similar gene prediction strategies, such as Piphillin2, PanFP3, and Tax4Fun2, the PICRUSt2 prediction method was deemed superior …”
Section: Materials and Methodsmentioning
confidence: 99%
“…The structure of the microbial community was determined by high-throughput sequencing of the 16S rDNA, according to previous research. 24 The samples were obtained from the reactors with CG, bio-M/CG, and abio-M/CG as the catalyst. The total DNA from samples was extracted using a FastDNA kit (BIO 101, Vista, CA) and then amplified by the specific primers (Bacteria: 341F-806R).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Previous studies have shown that Actinobacteria could effectively convert complex organic substrates into VFAs. 61 Also, Qin et al 62 reported that Actinobacteria are involved in the VFA formation process. Similar correlations of digestion substrates with microbial species and metabolic pathways were also found at the genus level and KEGG L3 (Figures S1 and S2).…”
Section: Variable Importance Analysis For Predicting Methane Productionmentioning
confidence: 99%
“…2 Apart from the pollution attribute, WAS also exhibited resource features due to the high organic proportion, which could be a promising feedstock for resource recovery. 3 Currently, anaerobic digestion is a widely accepted route for WAS treatment with methane (as a carbon-neutral sustainable fuel) production, which could be used for electricity or heat to reduce greenhouse gas emissions and fossil fuel consumption. The calorific value of pure methane per cubic meter is about 35,807 kJ, and the average power generation price using methane as a storage molecule is 0.18€/kW h. 4 As the microbial-dominated biological process, functional microorganisms exhibited vital roles in the anaerobic digestion process, and their microbial viabilities and activities were easily influenced by those undesirable ECs in WAS.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Because of the limited removal efficiency of conventional treatment processes, most ECs are eventually transferred and highly concentrated (even up to tens of mg/g dry matter) in the waste activated sludge (WAS), which exhibited great ecological risks . Apart from the pollution attribute, WAS also exhibited resource features due to the high organic proportion, which could be a promising feedstock for resource recovery . Currently, anaerobic digestion is a widely accepted route for WAS treatment with methane (as a carbon-neutral sustainable fuel) production, which could be used for electricity or heat to reduce greenhouse gas emissions and fossil fuel consumption.…”
Section: Introductionmentioning
confidence: 99%